Letter from Edward N. Kent to James Curtis Booth, September 18, 1855 - Kent, Edward (1855)
Edward N. Kent of the United States Assay Office at New York discusses monetary values of gold and silver ores retrieved via his newly invented sifting machinery.
Keywords: Booth, James Curtis, 1810-1888; United States Mint; Mint of the United States; United States. Assay Office, New York City